Realizing an Inclusive Campus: A Systematic Review of Support, Readiness, and Challenges in Providing Services for Students with Disabilities - Qurrotullain, Aini; Ridwan, Prinanda Gustarina; Effendi, Zulfa Rahmah (Universitas Pendidikan Indonesia (UPI), 2025)
This study aims to explore the types of services available for students with disabilities in higher education, analyze the factors influencing institutional readiness, and identify the major challenges faced by universities in providing these services. The research employs a Systematic Literature Review (SLR) method based on PRISMA guidelines, analyzing 20 empirical articles published between 2020–2025 from five leading academic databases. The findings reveal that universities have provided various services, including academic support, assistive technology, physical accommodations, and socio-emotional assistance. However, the implementation of these services remains highly dependent on institutional policies, human resource capacity, infrastructure, and inclusive campus culture. Major challenges include insufficient staff training, limited access to assistive tools, administrative bureaucracy, and persistent social stigma against disability. The implications of this study highlight the potential of its findings as a strategic basis for formulating or strengthening inclusion policies at the higher education level. Moreover, it underscores the urgency of continuous professional development for academic and administrative staff in adopting inclusive teaching strategies responsive to the diverse needs of students. Additionally, the high level of stigma and resistance within campuses suggests the need for institutional cultural transformation through sustained educational and advocacy programs.